Development Of Smart Polybutylene Adipate Terephthalate (PBAT) Blending For Plant Pot Application - Mahyudin, Muhammad Luqman Hakim (Universiti Sains Malaysia, 2022)
The objective of this research was to fabricate PBAT/Starch/PEG and dye that has halochromic properties via two roll mill and compression moulding techniques. The mixing of thymol blue and methyl red was used as pH dye and PBAT-starch was plasticized with polyethylene glycol (PEG) using heated two-roll mill. The halochromic properties of the PBAT/starch/PEG/Dye samples were characterized by visual response where the colour analysis was performed using CIE L*a*b* colour space model. The colour changes of halochromic sample were tested at different pH solution such as hydrochloric acid, boric acid, and sodium hydroxide solution. In addition, its reversibility halochromic properties were also investigated. It was found that sample change colour from orange to green when exposed to alkaline environment while it turns orange to dark orange in acid environment. The changes were rapid, within 1 minutes after exposure. However, its reversibility was tested with immerse sample for 30 min. It can be observed that by using naked eye, after 30 minutes dipping distilled water, the sample that was dipped into HCl and boric acid are successfully turn into light orange colour. However, for sample that was immersed in NaOH solution there is no obvious colour changes observed. Morphology of PBAT/starch/PEG/Dye were analysed by scanning electron microscopy (SEM). It can be concluded that the starch particle in PBAT/Starch/PEG/Dye became small when the amount of PEG increases. The properties of PBAT/Starch/PEG/Dye on the tensile properties were studied. The increasing amount of PEG has improved the mechanical properties such as tensile strength, elongation at break and tensile modulus.